THE IMPORTANCE OF BASIC ACCOUNTING KNOWLEDGE TO RURAL-BASED MICRO ENTREPRENEURS (Case of Bangladesh) - Mohammed N Alam (Universitas Trisakti, 2009)
The rural-based micro-entrepreneurs play a predominant role in generating job opportunities and solving unemployment in both least developed and developing nations of the world. In spite of its enormous contributions unfortunately, this sector of economy is found as a neglected sector in almost all developing nations. It is observed from the present research that besides financial needs the rural-based micro entrepreneurs requires knowing the basic knowledge in accounting so that they are capable of organizing their financial activities properly and maintaining records of their day to day monetary transactions. The paper reflects the results of an empirical study relating to the basic knowledge of different aspects of accounting among rural-based micro entrepreneurs in Bangladesh. The study also aimed at finding whether the rural-based micro entrepreneurs are conversant with recording their day to day transactions in the books of accounts and determine profit or loss of the firm accordingly. An 'Institutional Network's (Alam, 2002) theoretical approach and a qualitative research methodology are used to study this particular phenomenon.Keywords: basic accounting knowledge, rurol based micro entrepreneur